Book Review: Language Curriculum Design - Marlia, Marlia (Har Press Indonesia, 2022)
Book reviews are designed to enlighten readers about the content and quality of the book being reviewed. The goal of this paper is to study and critically analyze I.S.P. Nation and John Macalister's Language Curriculum Design book, which is the most widely mentioned and used work in the area. This book was broken into fourteen chapters by the reviewer. The first chapter serves as an introduction to future chapters. The fundamental procedures in the language curriculum design process are explained in chapters two through eight. Chapter nine discusses various approaches to covering these steps. Chapters ten through fourteen cover various aspects of language curriculum design. The review will include an assessment of the author's visual approach as well as the substance.